Recobrimento do solo e oferta de frutos por espécies arbóreas na restauração florestal - Almeida, Crislaine de (2017)
The approach used for forest restoration depends on the degraded ecosystem resilience. When sites have surpassed the thresholds of resilience, we need active restoration techniques, and the plantation of tree seedlings in the whole area is the most common one. A fast soil cover and a good animal-dispersed fruits supply are desirable characteristics for restoration plantings because they promote invasive grasses suppression and accelerate natural regeneration. However, if the selected species for planting are inappropriate, ecological succession may be not recovered and/or restoration may take a longer time and become more expensive. Thus, it is pertinent to understand how planted trees interact with the environment in restoration sites. This research aims to answer how tree species used for soil coverage promote floor shading and how animal-dispersed species provide fruits to seed dispersers in young forest restoration plantings. First, to assess floor shading, 14 species had their crown architecture and photosynthetically active radiation (PAR) interception evaluated in three years old restoration plantings. We compared PAR interception among species, seasons (dry and rainy) and areas and evaluated which crown architecture traits are the best predictors of PAR interception. Besides, to assess fruit provision, 17 animal-dispersed species in six three to eight years old sites were evaluated regarding age of first fruiting, periodicity and intensity of fruit production. We also evaluated if older sites had a higher and more uniform and intensity fruit production. We found that species differ in PAR interception for both the dry and the rainy season; PAR interception varies between sites for a given species and that for many species PAR interception varies between seasons, indicating that a good shading species in the rainy season sometimes is a poor shading in the dry season. Besides, for the rainy season, lower tree height and first branch height, and greater diameter at breast height and leaf size are the best predictors for PAR interception, while for the dry season the capacity of prediction is weaker and represented by lower tree height, greater crown area and greater leaf size. Older sites did not have a more uniform fruit production, and only threefrom 17 species produced fruits every month, being those the only ones with fruits in this season. Five species have not produced fruits until eight years old, indicating that a better selection of species is needed if we want a better fruit provision in young restoration plantings. In conclusion, not all the species considered as good shade trees so far, are in fact promoting a good PAR interception because this characteristic cannot be fully predict only by canopy structure traits. Thus, it is important to include other variables, such as foliar phenology and species’ responses to competition and to management and environmental conditions for the selection of good shading trees for restoration plantings. Moreover, not all planted animal-dispersed species have fruit provision (precocity, uniformity, and intensity) in young forest restoration plantings and this ability could be better used for selecting the best species for restoring functioning in degraded sites.